The The Effectiveness of IBL and PBL Models in Terms of Self-Confidence and Students’ Metacognitive Ability - Anggraheni, Fani Yunida (CV. Jendela Edukasi Indonesia, 2024)
This study aims to describe and compare the effectiveness of the IBL and PBL models in terms of students' self-confidence and metacognitive abilities. The research is carried out at SMA Negeri 1 Sewon class XI with the application material of algebraic function derivatives. The type of research used is an experiment with a quantitative approach, and the design used is quasi-experimental. The results showed that both IBL and PBL were effective the terms of self-confidence and metacognitive ability. Based on the comparison of learning models on self-confidence, there is no difference between the two models of the metacognitive ability of the PBL model is better than the IBL